METHODOLOGICAL BASIS FOR DEVELOPING DEONTOLOGICAL READINESS IN FUTURE SPECIALISTS - Kabulov , Azamat (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article provides a theoretical analysis of the methodological foundations for forming students' deontological readiness. The interdisciplinary links of deontology with philosophy, psychology, and higher education pedagogy are examined.